General Pharmacology Studies on ß-Domain Deleted Recombinant Factor VIII - Lee, Jang-hern; Kim, Hyun-woo; Kwon, Young-bae; Kang, Myung-soo; Choi, Dong-won; Na, Jun-ho; Kwon, Oh-kyung; Youn, Hee-jeong; Han, Ho-jae; Byun, Tae-ho; Park, Song-yong; Chun, Bok-hwan; Pyun, Jong-hwan; An, Gil-hwan; Lee, Young-jae; Cho, Myung-haing (Arzneimittelforschung, 2000)
ß-Domain deleted recombinant factor VIII (GC-rAHF), newly developed by Korea Green Cross Co., is a novel therapeutic for hemophiliacs and is currently under clinical evaluation. The general pharmacological properties of this drug were evaluated using mice, rats, guinea pigs and rabbits. Intravenous doses of 5 to 500 IU/kg were assayed in several tests to analyze their effects in vivo on various systems. The effect of the substance under study was also tested in vitro on isolated guinea pig ileum preparations at final concentrations of 5 to 50 IU/kg. The result of this study showed that GC-rAHF did not affect general behavior in the Irwin test. Similarly the drug was not found to affect neither normal body temperature nor the spontaneous activity in mice. In addition, it was not found to induce pharmacologically significant alterations of the cardiovascular and respiratory parameters in rats. No effects were observed either in the pentobarbital sodium-induced sleep-induction time and duration, in writhing test or in the test of pentetrazole-induced convulsion. Finally, the tested drug did not modify the gastrointestinal motility, acetylcholine or histamine-induced contraction of the isolated guinea pig ileum, nor gastric secretion.The results demonstrated that GC-rAHF has no effects on the central nervous, cardiovascular, respiratory and digestive systems in the doses of 5, 50 and 500 IU/kg in vivo and 5, 10, 50 and 100 IU/kg in vitro.
Keywords: ß-Domain deleted recombinant factor VIII, general pharmacology; Factor VIII, by genetic engineering technology